ANALYSIS OF THE EFFECT OF OPN UNEMPLOYMENT AND INFLATION ON PER CAPITA INCOME IN WEST KALIMANTAN FROM 2009 TO 2009 - B01112053, RAMADHAN (Jurnal Curvanomic, 2016)
Per Capita income is an indicator used to view the progress of development of countries in the world. The world Bank uses per capita income to classify countries in different income groups i.e. low income, lower middle income, middle income, upper-middle income, and high income countries so that income per capita can be used as an indicator of standard of living or welfare of the population of a country. The purpose of this study is to find out the effect of the rate of open unemployment and inflation on per capita income in the province of west Kalimantan in the period from 2009 to 2013. The data analysis technique used was multiple regression wit a fixed effect model. The data were obtained from the central Bureau of statistics. Partially, the rate of unemployment had a significant negative effect on per capita income. Inflaton had significant negative effect on per capita income. Simultaneously, the rate open unemployment and inflation had a significant effect on per capita income. Keywords: Per capita income, Rate of Unemployment, Inflation